STUDIES ON THE CULTIVATION OF THE STRAWBERRY UNDER THE LIGHT TRANSMISSION TYPE SOLAR CELL CONDITION - Tanaka, Takayuki; Kinouchi, Hitoshi; Akutsu, Masako (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
We examined the cultivation of the strawberry under the light transmission type solar cell (panel) condition that absorbs the ultraviolet light for electricity, and passes ca. 20% of visible light from 400nm to 800nm for photosynthesis. Though the color of leaves under the solar cell was lighter than that under control area, the length and width of the leaves were not so different among the treatments. On the other hand, the number of honeybees visiting flowers and SSC were significantly correlated with the integrated photon flux density, and the number of fruits harvested and the yield showed strong correlation coefficient with it. However, the coefficient of correlation between the number of flowers bloomed or fruit size and the integrated photon flux density were relatively low, suggesting that the light interception by the solar cell does not affect much on the number of flowers bloomed or fruit size. As the yield and the quality of the strawberry fruits decreased with the light intensity by the light transmission type solar cell, the yield and the quality of the fruits can be improved by widening the space between the panels. Originally, the transmission type solar cell had been expected not only as ecological role of power generation, but also as the source of light in a room. Here, the authors propose an additional role of the transmission type solar cell as a roof panel of a greenhouse.